Receptivity to and Recall of Alcohol Brand Appearances in U.S. Popular Music and Alcohol-Related Behaviors - Primack, Brian A.; McClure, Auden C.; Li, Zhigang; Sargent, James D. (Alcoholism, clinical and experimental research, 2014)
Background The average U.S. adolescent is exposed to about 2.5 hours of popular music and 8 mentions of alcohol brands every day. Alcohol brand mentions may function as advertising whether or not they are sanctioned by the alcohol industry. Our study aimed to determine associations between adolescents' involvement with music containing alcohol brand mentions and alcohol‐related behaviors. Methods In 2010 to 2011, we conducted a random‐digit‐dial survey using national U.S. land line and cell phone frames. Through screening interviews, we identified 6,466 eligible households with subjects between 15 and 23 years of age, of whom 3,422 (53%) completed the telephone survey. Of these, 2,541 opted to participate in a subsequent web‐based component. Independent variables included a composite score indicating owning and liking popular songs with alcohol brand mentions and correct recall of alcohol brands in songs. Outcome measures included ever having consumed a complete drink, ever bingeing, bingeing at least monthly, and having experienced problems from alcohol use. Results Among the 2,541 participants, compared with those in the lowest tertile on the receptivity scale, those in the highest tertile had higher odds of having had a complete drink (OR = 3.4; 95% CI = 2.2, 5.2) after adjusting for age, sex, race/ethnicity, socioeconomic status, sensation seeking, friend alcohol use, and parent alcohol use. Compared with those who did not identify at least 1 alcohol brand correctly, those who did had over twice the odds of having had a complete drink (OR = 2.1; 95% CI = 1.2, 3.8) after adjusting for all covariates. Results were also significant for the outcome of ever bingeing, but not for bingeing at least monthly or having had problems due to drinking. Conclusions In a national sample of U.S. adolescents and young adults, there were independent associations between involvement with popular music containing alcohol brand mentions and both having ever had a complete drink and having ever binged on alcohol.